Una tarda critica a Cartesio e Gassendi di un tomista dei primi del ’700: la Dissertatio de modis sciendi iuxta Chartesii et Gassendi discipulos - Stefano Caroti (Noctua)
This paper discusses an anonymous manuscript Dissertatio against Descartes’s and Gassendi’s theories of knowledge, dating from the first half of the eighteenth century and now preserved in the Biblioteca Forteguerriana in Pistoia. It is probably the result of Jesuit pedagogy, stemming from the lectures in which Aristotle’s works were commented on, drawing heavily on the doctrine of Thomas Aquinas.